Gut-joint axis: Gut dysbiosis can contribute to the onset of rheumatoid arthritis via multiple pathways - Romero-Figueroa, María del Socorro; Ramírez-Durán, Ninfa; Montiel-Jarquín, Alvaro José; Horta-Baas, Gabriel (Frontiers in Cellular and Infection Microbiology, 2023)
Rheumatoid Arthritis (RA) is an autoimmune disease characterized by loss of immune tolerance and chronic inflammation. It is pathogenesis complex and includes interaction between genetic and environmental factors. Current evidence supports the hypothesis that gut dysbiosis may play the role of environmental triggers of arthritis in animals and humans. The experiment results in animal models revealed that gut dysbiosis could shape the immune system and may contribute to the development of arthritis. Alterations in intestinal permeability and gut dysbiosis have been found to predate disease onset. However, the precise underlying mechanisms by which gut dysbiosis induces the development of arthritis remain elusive. This review aimed to highlight the mechanisms by which gut dysbiosis plays a role in the pathogenesis of RA. Evidence suggests that gut dysbiosis can contribute to increased inflammatory arthritis susceptibility by multiple pathways, including alterations in gut barrier function, molecular mimicry, gut dysbiosis influences the activation and the differentiation of innate and acquired immune cells, cross-talk between microbiota-derived metabolites and immune cells, and alterations in the microenvironment. The relative weight of each of these mechanisms in RA pathogenesis remains uncertain.